Epistemic modality : functional properties and the Italian system - Pietrandrea, Paola (Studies in language companion series, 2005)
This volume offers an original theoretical and methodological approach to the hotly debated issue of epistemic modality. The analysis is conducted in a rigorous typological frame developed after a careful consideration of a wealth of cross-linguistic data, and focuses on Italian, a language often disregarded in comparative analyses. The complexity of the Italian epistemic system provides relevant information that will undoubtedly foster a better understanding of the topic. A new definition of epistemic modality is proposed on a functional basis and the structure of the Italian epistemic system.